Description of a new genus and three species of Encyrtidae (Hymenoptera: Chalcidoidea) from the Western Ghats of Karnataka, India - Singh, Sudhir; Devi, O. K. Rema; Srinivasa, Y. B. (Zootaxa, 2014)
A new genus of Encyrtidae (Hymenoptera: Chalcidoidea), Noyesencyrtus Singh gen. nov. (type species N. brachyoculus Singh sp. nov.), associated with insects inhabiting fruiting bodies of wood-decaying fungi, and two new species, Psyllaephagus kundapurensis Singh sp. nov. and Ooencyrtus hayatii Singh sp. nov., are described from the Western Ghats of Karnataka, India.